Estudio sobre la creación de seis preparaciones de helados artesanales a base de frutos nativos andinos - Dávila Lima, Josué Salvador (2022)
The Andean fruits come from native plants adapted to the ecological conditions of the Andes, the nutritive value of these fruits is unique and mostly special, this work was proposed as the objective of developing the knowledge of the use of Andean native fruits through six artisan ice creams that promote the interest of the food heritage of Ecuador. In order to achieve this, the following research question was defined: To what extent does the use of Andean fruits influence the preparation of six artisan ice creams to promote the interest of Ecuador's food heritage? The methodology is developed, defining that the work is an applied investigation, with a mixed approach\; in which three types of documentary, experimental and applied research were addressed\; 164 people from the city of Atuntaqui belonging to the Antonio Ante canton, Imbabura province, were surveyed, as well as gastronomic experts and researchers were interviewed in order to gather the necessary information to develop a line of ice creams based on the proposed Andean fruits. The information was collected in the month of November 2020\; considering that the most relevant results were the following: a) the relative age that would consume this product are people between 18 and 30 years old, being people with economic solvency\; b) the ignorance of the Andean fruits in the population, most people have heard of this type of fruit, however, not many consume nor do they know the existing variety. It is concluded that there is a need to propose appropriate strategies and give key points on how to improve the management of Andean fruits, encourage and increase their consumption through the elaboration of products, proportions, initial support of the farmer and the contribution of the consumer.